A robust global MPPT to mitigate partial shading of triple-junction solar cell-based system using manta ray foraging optimization algorithm. (1st September 2020) - Fathy, Ahmed; Rezk, Hegazy; Yousri, Dalia
Highlights: A new MPPT based Manta ray foraging optimizer (MRFO) is proposed. The proposed MPPT is used for Triple-Junction solar based array operated under shadow conditions. Seven shadow patterns are studied on seven topologies of triple junction solar based arrays. Comparison to differential evolution (DE) and crow search algorithm (CSA) is performed. The MPPT based MRFO ensures tracking the global maximum power point (GMPP). Abstract: The high efficiency triple-junction solar cells (TJSC) have received considerable attention in the concentrated PV systems nonetheless the harvested electrical energy generated by TJSC-based system has been reduced under the partial shading conditions. Tracking the global maximum power point in the TJSC-based system characteristics is a main challenge faced the traditional trackers like perturb and observe (P&O). Therefore, this paper proposes a new global maximum power point tracker (MPPT) based on recent metaheuristic approach of Manta ray foraging optimization (MRFO). The proposed MRFO based MPPT is employed to extract the global maximum power point (GMPP) from the Triple-Junction solar based array operated under shadow conditions. Seven shadow patterns are studied on seven topologies of triple junction solar based arrays. The obtained results are compared with differential evolution (DE) and crow search algorithm (CSA). The obtained results confirmed the superiority of the proposed MPPT based MRFO in extracting the GMPP under different partial shadow patterns followed by CSA and DE optimizers.